2017
DOI: 10.1016/j.cub.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Sharp-Wave Ripples in Primates Are Enhanced near Remembered Visual Objects

Abstract: The hippocampus plays an important role in memory for events that are distinct in space and time. One of the strongest, most synchronous neural signals produced by the hippocampus is the sharp-wave ripple (SWR), observed in a variety of mammalian species during offline behaviors, such as slow-wave sleep [1-3] and quiescent waking and pauses in exploration [4-8], leading to long-standing and widespread theories of its contribution to plasticity and memory during these inactive or immobile states [9-14]. Indeed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 51 publications
5
69
0
Order By: Relevance
“…We did not explicitly evaluate object‐in‐scene memory per se in this study, thus the enhanced gamma synchrony early after scene onset may be considered a more general scene familiarity effect. Of note, higher‐frequency sharp wave ripples in these same brain regions are suppressed at the time of scene onset, and recover only later on, in association with remembered targets (Leonard and Hoffman, ). Taken together, this may suggest different modes of operation in the primate hippocampus as contextual cues emerge and recollection unfolds.…”
Section: Discussionmentioning
confidence: 99%
“…We did not explicitly evaluate object‐in‐scene memory per se in this study, thus the enhanced gamma synchrony early after scene onset may be considered a more general scene familiarity effect. Of note, higher‐frequency sharp wave ripples in these same brain regions are suppressed at the time of scene onset, and recover only later on, in association with remembered targets (Leonard and Hoffman, ). Taken together, this may suggest different modes of operation in the primate hippocampus as contextual cues emerge and recollection unfolds.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional phenomena relevant to anticipatory effects have been reported previously. First, it was observed that sharp wave ripples were enhanced near remembered visual objects (Leonard and Hoffman, 2017). Second, oscillatory activity was found to synchronize with visual exploration, through a theta phase reset at saccades (Hoffman et al, 2013;Jutras et al, 2013).…”
Section: Idiothetic (Self-motion) Update Of Spatial View Cellsmentioning
confidence: 99%
“…Critically, the reliability of theta phase-reset by visual fixations correlated with successful memory formation [31]. Furthermore, other neural signals of memory processing by hippocampus include sharp-wave ripples [33], which have been observed during visual exploration in the nonhuman primate [34], particularly for fixations in close proximity to target stimuli in a memory task [35]. In studies with rodents, memory is usually expressed via exploration, making it difficult to determine the extent to which hippocampal activity in these studies reflects memory processing versus exploration, including sensory sampling and exploration-related aspects of spatial navigation [36].…”
Section: Evidence Linking the Hippocampus To Viewing Behaviormentioning
confidence: 99%